Exploring the Needs and Challenges in Teaching English Grammar Communicatively in Albanian Context - Koca, Suela; Benita Stavre; Lindita Kacani (International Journal of Language and Literary Studies, 2024)
The aim of this study is to explore through details of teaching English grammar communicatively within the Albanian context. With the global trend for communicative language teaching, Albanian teachers of English as a foreign language face specific challenges in attempting to integrate this approach effectively in their classes. The research applies a mixed-methods approach, including a questionnaire and structured interviews with teachers from several districts in Albania. Both cases intend to assess the actual situation of teaching grammar of English as a Foreign Language, identify main obstacles, and highlight opportunities for integrating communicative grammar. Findings indicate that even though the teachers are aware of the theoretical aspects of communicative methods, sometimes they find it hard to implement them due to limited resources, insufficient teacher training, and traditional teaching curricula. Additionally, the study emphasizes the need for professional development programs and appropriate classroom materials that align with the communicative approach. By addressing these challenges, the research aims to provide concrete recommendations for teachers and policymakers to improve English grammar teaching in Albanian schools, so as to improve language proficiency and communicative competence among learners of different ages and educational levels in a larger context.